TECHNO-BUREAUCRATIC GOVERNANCE AND DEVELOPMENTAL STATE IN AFRICA: BOTSWANA AND NIGERIA IN COMPARATIVE PERSPECTIVE - Paul-Sewa Thovoethin (European Scientific Journal, ESJ, 2014)
This work uses developmental state’s paradigm in explaining how development in the Third World should be understood as a process in which states have to play strategic roles in planning and sustaining economic development. By comparing Botswana and Nigeria, the work establishes how the nature and character of techno-bureaucratic governance become necessary in the emergence and sustenance of developmental state in Africa. Such developmental oriented technocracy and bureaucracy should not only be autonomous and constitute the Weberian ideal bureaucracy, but must also be powerful, highly professional and technically competent.